Nephelauxatic Effect of Telluro Ether Complexes of Co(II), Ni(II) and Cu(II) - K. Singh, Amit; Pd. Sinha, Sudhir; Kumar , Vijay; Rai, S.S.; Sharma, S. (Asian Journal of Chemistry, 2011)
Chalcogens are known to be good ligands. Telluroethers of molecular formula 1-(N-Me)-2- (TeC6H4-4'-R)-4-MeC6H3. (where R=H, -OCH3 and -OC2H5) were prepared and they were used for complexation with Co(II), Ni(II) and Cu(II) metal ions. On the basis of IR and NMR, the ligands were found to coordinate through nitrogen and tellurium of the ligands. The10 Dq values of Co(II) complexes were found in the range of 9,774 to 10,388 cm-1, while for Ni(II) complexes the values were in the range of 9,220 to 9,290 cm-1. Cu(II) complexes show 10 Dq values in the range of 14,200 to 14,700 cm-1. In Co(II) complexes nephelauxatic effect, β35, was the lowest (3 %) for ligand having R=H and for R= -OCH3 and -OC2H5, it was very close to each other, i.e., 5.35 for -OCH3 & 4.91 for -OC2H5. However in Ni(II) complexes, β35 was almost same for R=H & -OC2H5 while it was lowest for R= -OCH3.